An application of technical requirements for the University of the Philippines Film Institute Film Archives a plan for structural and operational improvements - Santos, Efer Jhan Margarett C.; Rey, Emma M. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2006)
The University of the Philippines Film Center (UPFC) Film archives was duly recognized by UP through the study done by Annella Mendoza (1990), entitled "A Feasibility Study for the Operation of a Filipino Film Archive facility in the Film Center of the University of the Philippines." Mendoza's study presented the technical, market and financial aspects of the operations of the UPFC Film Archives. This feasibility became the blueprint for the operations of the Archives as an institution where the appreciation and the preservation of the film heritage can be seen. Mendoza's study in itself had adequately addressed the operational needs and requirements of the Film Archives but still, there were issues and problems that have greatly affected the operations and the implementation of the said study.
The study investigates the implementation of the technical requirements of the study by Mendoza. Through this investigation, it would assess the current status of the UPFC Film Archives and, eventually, come up with recommendations that would be used to improve the current state of the Archives.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Film Center (UPFC) Film Archives